2016
DOI: 10.18321/ectj309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Breakdown of South Gabal EL A’urf Polymineralized ore Material

Abstract: The polymineralized ore material of south Gabal El-A’urf area hosts several economic minerals. These include tanteuxenite, monazite, bastanasite, anatase, as well as zircon. The corresponding interesting rare metals of these minerals include Nb, Ta, lanthanides (REE), Ti, and Zr. Different breakdown techniques have been investigated namely; agitation, pug and fusion. The latter technique is found to be preferred under the following conditions; potassium bisulphate ore/reagent weight ratio of 1/3 at 650 ºC for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, alkali roast and leach dissolution method employing KOH roasting and H 2 O leaching on a low-grade Nb-Ta mineral ore has had great recoveries [44,47]. KHSO 4 fusion as a pyrometallurgical process to improve the subsequent leaching efficiency of a low grade Nb/Ta polymineralized ore has also been adopted [62]. The study reported the feasibility of Ta/Nb decomposition and leach recovery efficiencies of alkali dissolution process on low-grade minerals.…”
Section: Literature Overview Of the Pyro-hydrometallurgical Recovery ...mentioning
confidence: 99%
“…However, alkali roast and leach dissolution method employing KOH roasting and H 2 O leaching on a low-grade Nb-Ta mineral ore has had great recoveries [44,47]. KHSO 4 fusion as a pyrometallurgical process to improve the subsequent leaching efficiency of a low grade Nb/Ta polymineralized ore has also been adopted [62]. The study reported the feasibility of Ta/Nb decomposition and leach recovery efficiencies of alkali dissolution process on low-grade minerals.…”
Section: Literature Overview Of the Pyro-hydrometallurgical Recovery ...mentioning
confidence: 99%
“…Using H 2 SO 4 /HNO 3 acid mixture agitation leaching, almost complete dissolution of Nb and Ta was achieved together with 86% of Th and 70% of the REE; however, U and Ti leaching efficiencies did not exceed 60%. On the other hand, El Hazek et al [10] have applied different breakdown techniques including agitation with conc. H 2 SO 4 and potassium bisulfate fusion upon a polymineralized material to dissolve its metal values.…”
Section: Introductionmentioning
confidence: 99%
“…Through the investigation of effect factors, the optimum conditions were obtained and the leaching recoveries of niobium and tantalum were about 94.7 % and 93.6 %, respectively. Also, some other methods, i.e., KHSO 4 roasting [22], were also developed to enhance the leaching of Nb and other metals. For example, El-Hazek et al [22], studied the recovery of Nb and other valuable metals from polymineralized ore material of (containing 1.25 wt% Nb 2 O 5 , 0.19 wt% Ta 2 O 5 ) south Gabal El-A'urf area in Egypt using potassium bisulfate fusion, and they realized a high dissolution efficiencies for Nb of 98.0 %, Ta of 99.3 % and rare earth metals of 100 %, respectively.…”
Section: Introductionmentioning
confidence: 99%